Physico – Morphological Characteristics and Fertilizing Ability Studies on Semen of Holstein Friesian Bull - Saini, Jyoti; Dhande, P. L.; Gaikwad, S. A.; Shankhapal, V. D.; Patil, A. D. (Indian Journal of Veterinary Anatomy, 2018)
Semen samples from apparently healthy and sexually matured six Holstein Friesian bull were collected using artificial vagina as per the standard practice. The ejaculates were evaluated and characterized for various physico – morphological characteristics as well as in – vitro fertility using hypo – osmotic swelling tests. Seminal attributes i.e. the average semen volume, colour, consistency, pH, average sperm concentration, average initial motility, average live sperm count, abnormal sperm count, methylene blue reduction test and sperm membrane integrity of Holstein Friesian were 7.67±1.12 ml, Creamy white, Medium – thick, 6.55±0.06, 1119.00±46.74 millions/ml, Good (90%), 81.50±2.13%, 10.67±0.49%, 4.38±0.20 minutes and 87.67±2.08% respectively. It can be concluded that semen of Holstein Friesian bull was of good quality. Hence, it may be utilized for freezing and further use in propagation and development of the respective breeds.